Blockade of the TLR4–MD2 complex lowers blood pressure and improves vascular function in a murine model of type 1 diabetes - de Oliveira, Amanda Almeida (Sci Rep, 2020)
While the pathogenesis of diabetes-induced high blood pressure (BP) is not entirely clear, current evidence suggests that Toll-like receptor 4 (TLR4) is a key player in the mechanisms associated with hypertension. However, it is unknown whether this receptor affects BP under type 1 diabetes. Likewise, there is insufficient knowledge about the role of TLR4 in diabetes-associated vascular dysfunction of large arteries. To narrow these gaps, in this study, we investigated if blockade of the TLR4-MD2 complex impacts BP and vascular function in diabetic rats. We injected streptozotocin in male Sprague Dawley rats and treated them with a neutralizing anti-TLR4 antibody for 14 days. BP was directly measured in conscious animals at the end of the treatment. In another set of experiments, we excised the aorta from control and diabetic animals, and measured TLR4 and MD2—a co-receptor that confers functionality to TLR4—levels by Western blotting. We also performed functional studies and evaluated ROS levels with and without a pharmacological inhibitor for TLR4 as well as for MD2. Additionally, we scrutinized a large human RNA-Seq dataset of aortic tissue to assess the co-expression of TLR4, MD2, and subunits of the vascular NADPH oxidases under diabetes and hypertension. We report that (a) chronic blockade of the TLR4–MD2 complex lowers BP in diabetic animals; that (b) type 1 diabetes modulates the levels of MD2 expression in the aorta, but not TLR4, at least in the conditions evaluated in this study; and, that (c) acute inhibition of TLR4 or MD2 diminishes vascular contractility and reduces oxidative stress in the aorta of these animals. In summary, we show evidence that the TLR4–MD2 complex is involved in the mechanisms linking type 1 diabetes and hypertension.